TRANSFORMASI PENDIDIKAN TASAWUF DALAM TRADISI ISLAM MELAYU DI ERA MODERNITAS - Helmi Handoko; Cukup Islamiarso; Abdullah Idi; Muhammad Abdillah Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the transformation of Sufism education in the contemporary Malay Islamic tradition, focusing on the shift in methodological paradigms and the resilience of traditional values ​​amidst digitalization. Using a qualitative, descriptive-analytical approach, data were collected through participant observation, in-depth interviews with murshids and educational figures in Palembang, and a documentary study of classical manuscripts. The results demonstrate an epistemological reconstruction in which Sufism has transformed into an active and inclusive